Creating a high‐skills society during recession: issues for policy makers. (December 2015) - Panagiotakopoulos, Antonios
Abstract : The present study looks at the skill formation policies adopted by policy makers in Greece in order to create a high‐skills society. It examines empirically the demand side of the skill creation process within 300 small enterprises in order to understand how far supply‐side measures have influenced the demand for well‐trained staff within small businesses. The article draws on empirical data from 650 interviews with workers and small firm owners that explored owner demand for higher level skills and training. The study questions the effectiveness of the measures put forward by policy makers in order to encourage an up‐skilling strategy in the country. The analysis reveals that this policy agenda has been supported predominantly by various skills supply‐side initiatives including investments in higher education and subsidized accredited company training. Yet the empirical evidence indicates that such initiatives have not so far influenced owner demand for higher level skills and training, suggesting a new agenda for policy intervention may be necessary. The study provides valuable lessons for policy makers across the advanced capitalist world on the development of a high‐skills society.